Terminologia e documentação: um estudo terminográfico sobre performance musical - Soraia de Andrade Lara Carvalho (2013)
Controlled vocabularies used for music information retrieval and representation do not really match specialized languages used in scientific publications. This research aims to verify the possible Terminology contribution to the definition of conceptual fields in the Music area, in need of reference works to construct registration languages. The foundations of the General Theory of Terminology and the Communicative Theory of Terminology were adopted to develop a terminographic work, with the following procedures: selection of Music as the research area, subordinate area musical performance, and the choice of Articles published in 2012, in three representative Brazilian Music periodicals: Revista Per Musi, Revista Música Hodie e Revista Opus, as well as works presented in the Anppom Congress, in its Anais da Anppom 2012, a total of 144 documents as the corpus research. The occurrence of terms was identified and a manual collection and transcription was made studying their use in context. The data analysis showed there is a meaningful collection of terms adjacent to the term musical performance that can be categorized as specific subjects to constitute a homogeneous and representative vocabulary for the area. A terminological variation was identified and the conceptual relations between the terms established, showing different ways of treatment for the concept musical performance given in scientific texts about the subject. The terms were organized based on the specialized languages demonstrating that when we work with words used by specialists in their texts, it is possible to get the necessary matching between the vocabulary used for information representation and the universe of knowledge expressed in documents.